Bani Ma'shum: Identitas Keluarga Besar dan Kontestasi Kapital - Maulidia, Hanifa (Muqoddima: Jurnal Pemikiran dan Riset Sosiologi, 2020)
This article describes the identity of a Javanese Muslim family, Bani Ma’shum. The word Bani is adopted from the Arabic concept which means descendant. The social context of this sociological phenomenon is the local community of Jatibarang Brebes, Central Java, where most of the Muslim community members are affiliated with NU. As the identity of an extended family based on NU, the agents and members of the Bani Ma’shum utilize their identity and capital in their daily lives. This paper uses qualitative methods to explain the three capitals owned and utilized by the Children of Ma’shum. In cultural capital, most members of the Bani Ma’shum family took an Islamic based education, starting with Madrasah Ibtidaiyah (MI), which continued to both traditional and modern pesantren, and continued to state and private tertiary institutions. The symbolic capital of the members of the Bani Ma’shum family comes through the prestige of a distinguished family, because many of the Bani Ma’shum members are religious figures and social figures of Jatibarang. In political capital, that the first child of H. Ma’shum had ever served as the village head of Jatibarang, namely H. Abdul Halim. The three capitals are contesting in the field socio-religious, economic and political arena in Jatibarang Brebes, Central Java. By having these three capital, strengthening the social capital owned by the members of Bani Ma’shum, because it can strengthen the network,trust and norms that bind the members of the Bani Ma’shum extended family.